2021
DOI: 10.37763/wr.1336-4561/66.2.221230
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Adhesive Impurities of the Recovered Paper in Flotation Process

Abstract: The article presents results of the elimination of sticky impurities from recovered paper in laboratory flotation of three pulp suspensions with different whiteness, obtained directly from the production line before entering flotation. A combination of commercial agents releasing undesirable substances from recovered paper and means for regulation and stabilization of froth and modified micronized bentonit was used. In the flotation purification of pulp suspension with a whiteness of 53%, the combination of Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Yet, previous studies have suggested that the physicochemical properties of wastes, such as hydrophobicity and repulpability could impact their chemical and physical interaction with the fibre matrix and, in turn, the properties of the recycled containers 16,17 . However, most of the dedicated research efforts in the field have developed or improved strategies to efficiently remove the increasing amount of non‐fibrous materials (e.g., stickies) from recycled furnishes in order to decrease their impact on the appearance and performance of recycled paper‐based products 18,19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, previous studies have suggested that the physicochemical properties of wastes, such as hydrophobicity and repulpability could impact their chemical and physical interaction with the fibre matrix and, in turn, the properties of the recycled containers 16,17 . However, most of the dedicated research efforts in the field have developed or improved strategies to efficiently remove the increasing amount of non‐fibrous materials (e.g., stickies) from recycled furnishes in order to decrease their impact on the appearance and performance of recycled paper‐based products 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, most of the dedicated research efforts in the field have developed or improved strategies to efficiently remove the increasing amount of non-fibrous materials (e.g., stickies) from recycled furnishes in order to decrease their impact on the appearance and performance of recycled paper-based products. 18,19 Herein, we provide a deeper understanding of how variations in the physicochemical properties of waste can alter the performance of recycled containers and how to use this knowledge to further exploit their presence in recycled products. Valorization of these large quantities of waste through packaging design is a proposed sustainable route to endow recycled containers with a higher environmentally friendly profile.…”
Section: Introductionmentioning
confidence: 99%